Effects of processing parameters on furan formation in canned strawberry jam. (1st October 2021) - Shen, Mingyue; Liu, Lichun; Zhang, Fan; Jiang, Yujie; Huang, Zhengbo; Xie, Jianhua; Zhong, Yadong; Nie, Shaoping; Xie, Mingyong
Highlights: The pathway of furan formation in real system - canned strawberry jam was proposed. Citric acid added as an acidity-regulating agent could promote furan formation. Sugar rather than ascorbic acid is main precursor to form furan in strawberry jam. Adding thickening agents such as xanthan gum could mitigate furan formation. Sucrose or glucose would be better choice than fructose or high-fructose corn syrup. Abstract: The formation mechanism of furan has been studied extensively in model systems, however, furan formation in real foods are complex and far from being fully understood. In this study, the effects of acid-regulating agent (citric acid), sugar addition (glucose, fructose and sucrose) and thickening agents (xanthan gum, κ-carrageenan and pectin) on furan levels in strawberry jams were studied; meanwhile the formation pathway of furan in canned strawberry jam was proposed by carbon module labeling (CAMOLA) technique. Our results suggested low pH promoted furan formation in strawberry jam. Besides, fructose produces more furans than sucrose and glucose, and the addition of xanthan gum reduced furan levels significantly. The kinetic data showed that ascorbic and dehydroascorbic acid degradation followed first-order kinetics while rate of furan formation followed zero-order kinetics. This study presented the possibility of mitigating furan formation in canned strawberry jams by optimization of processing parameters and addition of xanthan gum.